Romans and the apologetic tradition: the purpose, genre and audience of Paul's letter - Guerra, Anthony J. (Society for New Testament Studies monograph series, 1995)
Of all the letters in the Pauline corpus, the Letter to the Romans has attracted the greatest degree of scholarly attention. Yet surprisingly scant consideration has been given to the question of its literary genre. Taking up the comparatively brief suggestions of previous scholars, Dr Guerra argues that the Letter belongs to the protreptic genre - the class of writing in antiquity which urges the adoption of a particular way of life (or a deeper commitment to it), setting out its advantages, replying to objections, and demonstrating its superiority. Working through each chapter of the Letter in turn, he indicates how Paul provides a critique of non-Christian ways of life (both Jewish and Gentile) and affirms the superiority of the Christian Gospel. It becomes apparent that the Pauline apologetics of Romans stand between the hellenistic Jewish tradition and the later Greek Christian apologists, and may have influenced the latter.